2010
DOI: 10.3390/s100605872
|View full text |Cite
|
Sign up to set email alerts
|

An RFID-Based Intelligent Vehicle Speed Controller Using Active Traffic Signals

Abstract: These days, mass-produced vehicles benefit from research on Intelligent Transportation System (ITS). One prime example of ITS is vehicle Cruise Control (CC), which allows it to maintain a pre-defined reference speed, to economize on fuel or energy consumption, to avoid speeding fines, or to focus all of the driver’s attention on the steering of the vehicle. However, achieving efficient Cruise Control is not easy in roads or urban streets where sudden changes of the speed limit can happen, due to the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 13 publications
1
74
0
1
Order By: Relevance
“…He found that properly designed ISA (Intelligent Speed Assistance) systems can be highly effective in encouraging motorists to obey speed limits and should be encouraged by governments. Pérez et al [3] presented a new Infrastructure to Vehicles (I2V) communication and control system for intelligent speed control, which is based upon Radio Frequency Identification (RFID) technology for identification of traffic signals on the road. Their results suggested that an automatic intelligent speed control system can be used to prevent any unexpected traffic circumstances and improve the safety of the occupants of the vehicle.…”
Section: Previous Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…He found that properly designed ISA (Intelligent Speed Assistance) systems can be highly effective in encouraging motorists to obey speed limits and should be encouraged by governments. Pérez et al [3] presented a new Infrastructure to Vehicles (I2V) communication and control system for intelligent speed control, which is based upon Radio Frequency Identification (RFID) technology for identification of traffic signals on the road. Their results suggested that an automatic intelligent speed control system can be used to prevent any unexpected traffic circumstances and improve the safety of the occupants of the vehicle.…”
Section: Previous Investigationsmentioning
confidence: 99%
“…(1) First example [3] It is an intelligent speed controller that is based upon Radio Frequency Identification (RFID) technology for identification of the traffic signals on the road. The operation of the RFID subsystem onboard the vehicle is described with the block diagram of Fig.…”
Section: Examples Of Automatically-set Road Speed Limiter (Rsl) Figmentioning
confidence: 99%
“…It is well-know that, as velocity sensor, the GPS does not represent and optimal option; however, since Molinero does not have an electronic calculator on board, the velocity estimation through DGPS is the simplest option with best results. As future work, it is being considered to install an electronic velocity sensor as the one described on [13].…”
Section: Electric Bus Descriptionmentioning
confidence: 99%
“…Likewise, a new infrastructure to vehicle communication and control systems for intelligent speed control, which is based upon RFID (radio frequency identification) technology for recognition of traffic signals on the road, and high accuracy vehicles speed measurement with Hall Effect-Based Sensor is explained in Ref. [4]. To achieve a more efficient adaptation of the speed of the vehicle, the approach introduces an adaptation of a fuzzy logic controller based on sensor fusion of the information provided by the infrastructure installed on the road.…”
mentioning
confidence: 99%
“…For instance, improving traffic-flow conduces to increase the service provided by the roads avoiding traffic jams and is reflected in a positive effect on the environment and the economy [1]. Some researchers have shown that these models produce realistic behavior [2][3][4][5]. According to this, the presented approach introduces a methodology capable of making flexible and autonomous decisions to adjust the green light interval of a traffic light signal, to the requirements of the road at any cycle of the phase.…”
mentioning
confidence: 99%